PENGARUH MODEL PEMBELAJARAN PBL DAN SNOWBALL THROWING TERHADAP PRESTASI DAN MOTIVASI BELAJAR SISWA DI SMK N 2 WONOSARI - Amin Nurmansyah; Sukaswanto Sukaswanto (Jurnal Pendidikan Vokasi Otomotif, 2020)
The purpose this research to determine the effect of the use of the Snowball Throwing learning model and the Problem Based Learning (PBL) learning model on student achievement, and determine the effect of using the Snowball Throwing learning model and Problem Based Learning (PBL) learning model on student motivation. Data collection techniques used in this study were using tests and questionnaires. The instrument validation test uses construct validation and content validation is conducted by the thesis supervisor. The results showed that the first research hypothesis stated Ha was accepted and Ho was rejected. The average value of PBL class learning achievement is 78.34 and Snowball Throwing class is 83.61. Thus the Snowball Throwing learning model has a positive effect on student achievement. For the second research hypothesis states Ha is rejected and Ho is accepted. Thus the Snowball Throwing learning model does not have a positive effect on the level of student motivation. The average value of PBL class learning motivation level is 75.40 and Snowball Throwing class is 72.68.